Box Fractal as an Iterated Function System in Fractal Interpolation for Determining the Approximate Value of Demand Data - Eka Susanti; Oki Dwipurwani; Dian Cahyawati; Novi Rustiana Dewi; Husnul Khotimah; Wahyuni Apria Ningsih (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2026)
A common problem in inventory planning is the uncertainty of demand. One technique for determining the demand approximation value is the fractal interpolation. The aim of this study is to develop a fractal interpolation technique using a Fractal Interpolated Function constructed by the affine function that forms the Box Fractal shape. The developed method is applied to interpolate rice demand data based on prices at a rice milling factory. Mean Absolute Percentage Error (MAPE) is used to measure the accuracy of the interpolation results. For the n^{th} iteration, the number of boxes formed is 5^n, and the number of pairs of points is 4×5^n. Based on the rice demand data from one of the factories, the best MAPE was obtained at the $6^{th}$ iteration, with a value of 16.319%, which falls into the good category. Based on the data used, the affine function forming the Box Fractal as a Fractal Interpolated Function can be applied in fractal interpolation techniques.